Field evaluation of onsite near real-time monitors for surface contamination by 5-fluorouracil - Smith, Jerome P (J Oncol Pharm Pract, 2018)
OBJECTIVES: In order to produce near real-time onsite results to detect surface contamination by antineoplastic drugs, the National Institute for Occupational Safety and Health developed monitors for 5-fluorouracil, which use surface wiping and lateral flow immunoassay for measurement. The monitors were tested in the laboratory to assess the sensitivity of detection on laboratory-produced contaminated surfaces. A field evaluation to assess the capability of the monitors to make measurements in healthcare workplaces was carried out in collaboration with a medical device company and the results are presented in this report. METHODS: The 5-fluorouracil monitor was evaluated in areas where oncology drugs were prepared and administered to patients at five different hospitals. The levels of contamination measured with the monitors were compared to levels measured with liquid chromatography-tandem mass spectrometry. RESULTS: The 5-fluorouracil values measured with the liquid chromatography-tandem mass spectrometry ranged from 0 to over 200,000 ng/100 cm(2). Measurements by the 5-fluorouracil monitors in the range 10–100 ng/100 cm(2) correlated with the liquid chromatography-tandem mass spectrometry. Receiver operating characteristic curves developed for the data indicated that a positive limit of 22 ng/100 cm(2) would give an acceptable level of false-positives while retaining most true-positive samples. If the liquid chromatography-tandem mass spectrometry measured greater than 100 ng/100 cm(2), then the monitors also measured levels greater than 100 ng/100 cm(2) for the majority of samples. CONCLUSION: The data indicate that there are many areas in hospitals that are contaminated with 5-fluorouracil and the monitors will be useful in identifying this contamination.